REKONSTRUKSI TEOLOGI SOSIAL BERDASARKAN TORAH TERKAIT KEHADIRAN KRISTIANI DALAM ISU PELANGGARAN HAM - Grets Janialdi Apner (P3TK, Sanata Dharma University, 2022)
AbstractThis article offers a reconstruction of social theology in Christianity as a theological response to human rights violations in Indonesia. Human rights are universal and fundamental in humanity issues that can be a locus for Christians to do theology. For this reason, any forms of human rights violation are not just a violation of law and social orders but also theological issues that require an earnest response from religious people, including Christians. Therefore, the reconstruction of social theology in this writing will be using the biblical study method of the Torah and its role in the ancient Israelites’ context and a critical analysis of the concept of Christian presence. In these two interrelated methods, the author wants to define the Christianity values, which indicate theological positions towards human rights violations in Indonesia, and point out the Christians’ characteristics that present faith works and the integrity of life. This writing then consists of three parts. The first part explains the concept of human rights and a portrait of human rights violations in Indonesia. Second is the Torah’s proper hermeneutics and role in the ancient Israelites. Third, at last, a critical analysis of the concept of Christian presence as the embodiment of faith concerning human rights violations. The Christian presence in the human rights issues, especially in human rights violations, is not only a social responsibility as Christians before God but also a tangible manifestation of faith in the context of Indonesia. Therefore, the author argues that it is essential for Christians to develop their sensitivity and actively respond to human rights violations.AbstraksiArtikel ini menawarkan rekonstruksi teologi sosial dalam agama Kristen berdasarkan peran Taurat sebagai respon teologis terhadap pelanggaran hak asasi manusia di Indonesia. Pelanggaran hak asasi manusia adalah masalah mendasar kemanusiaan yang melanggar hukum dan pelecehan sosial. Isu ini bersifat teologis karena kehadiran umat Kristiani dibutuhkan sebagai respon. Rekonstruksi teologi sosial dalam tulisan ini akan menggunakan metode studi biblika tentang peran Taurat dalam konteks Israel kuno dan analisis kritis terhadap konsep kehadiran Kristen. Berdasarkan dua metode yang saling terkait tersebut, penulis ingin mendefinisikan nilai-nilai agama Kristen, yang menunjukkan posisi teologis terhadap pelanggaran hak asasi manusia di Indonesia. Tulisan ini terdiri dari tiga bagian. Bagian pertama menjelaskan konsep hak asasi manusia dan menggambarkan pelanggarannya di Indonesia. Kedua, interpretasi Taurat dan perannya dalam budaya Israel kuno. Ketiga, analisis kritis terhadap konsep kehadiran umat Kristiani sebagai pengejawantahan iman terhadap pelanggaran hak asasi manusia. Oleh karena itu, penulis berpendapat bahwa menanggapi pelanggaran hak asasi manusia sangat penting bagi orang Kristen untuk mengembangkan kepekaan dan tanggung jawab mereka terhadap pelanggaran hak asasi manusia. Kehadiran umat Kristiani dalam pelanggaran HAM merupakan bentuk tanggung jawab sosial sebagai umat Kristiani di hadapan Tuhan dan manifestasi iman dalam konteks Indonesia.